Improving The Compliance With Accounting Standards Without Public Accountability (SAK ETAP) By Developing Organizational Culture: A Case Of Indonesian SMEs - Yanto, Heri; Yulianto, Arief; Sebayang, Lesta Karolina Boru; Mulyaga, Fian (Journal of Applied Business Research, 2017)
In Indonesia’s economy SMEs have significant contribution to GDP and labor employment. On the other hand, SMEs still have substantial problems. One of them is related to capital insufficiency due to limited access of SMEs to financial institutions. This limitation may be caused, among other things, by the fact that SMEs’ financial statements have not complied with Accounting Standards without Public Accountability (SAK ETAP). The study aims at identifying antecedents of SAK ETAP implementation as well as formulating strategies to improve its implementation in SMEs. Five important antecedents of SAK ETAP implementation are organizational culture, education, exposure, age, and scale. Therefore, developing organizational culture by increasing SMEs’ exposure on socialization and training is a promising strategy. There is also a need for more intensive cooperation of various parties such as government, Institute of Indonesian Chartered Accountants (IAI), universities, SME association, and NGOs to improve both SMEs’ compliance with SAK ETAP and organizational culture. In addition, mobilization of academic staffs and accounting students to facilitate the implementation of SAK ETAP is worth-trying.
Keywords: SAK ETAP Implementation; Organizational Culture; Indonesian SMEs